Vacuum packaging: A promising technology for safe storage of green gram (Vigna radiata) seeds - THAKUR, VIJAYSINGH; C M, NAWALAGATTI; M B, CHETTI; J S, HILLI; PATIL, R V (The Indian Journal of Agricultural Sciences, 2025)
Storage investigations were carried out for 18 months from 15 November 2019, to 15 May 2021 at the University of Agricultural Sciences, Dharwad, Karnataka to assess the impact of cloth, gunny, high-density polythene (HDPE) and vacuum-packed bags under ambient and cold conditions on the seed health of green gram. The rate of seed deterioration (26%), even in cold storage, owing to their permeable nature. Conclusively, the present study affirms that vacuum packaging emerges as the superior and promising technology when contrasted with numerous traditional packaging methods, ensuring the secure storage of green gram seeds in a natural, chemical-free environment. Consequently, not only does it contribute to the prolonged maintenance of seed health, but it also effectively eliminates any environmental threats.